Summer school [videorecording (DVD)] - West, Howard (Television producer); Birnbaum, Stuart; Dashev, David; Franklin, Jeff, 1955-; Harmon, Mark, 1951-; Alley, Kirstie; Thomas, Robin, 1953-; Labyorteaux, Patrick, 1965-; Thorne-Smith, Courtney; Cameron, Dean; Riley, Gary; Minter, Kelly; et al. (Paramount Home Entertainment, 2017)
Freddy Shoop is a high school gym teacher who has big plans for the summer. He is forced to cancel them to teach a summer remedial English class to a bunch of misfit goof-off students. Fortunately, his unconventional brand of teaching and fun field trips begins to connect with them. Even inspiring ardor in some.